Why Do Manufacturing Firms Sell Services? Evidence from India - Grover, Arti (World Bank, Washington, DC, 2021)
Manufacturers in India are increasingly selling services—a phenomenon referred to as servitization. Both the proportion of manufacturers selling services and the share of services in total revenue of manufacturers increased threefold between 1994 and 2013. More productive manufacturers and those more exposed to import competition are more likely to sell services and to obtain a higher share of their revenue from services. A 10 percent increase in servitization is associated with 2.6 percent increase in manufacturing revenue. However, servitizing firms suffer a greater contraction in manufacturing revenue with increased import competition. This evidence suggests that servitization is not a successful defensive strategy to maintain manufacturing sales in the face of import competition, and it is more likely to be an exit strategy to flee import competition. Corroborative results indicate that past services sales are positively associated with the introduction of new services products and eventually a switch out of manufacturing and into services as the primary activity. Thus, servitization appears to be an aspect of “premature deindustrialization” in India, driven by the inability of manufacturers to cope with import competition, rather than structural transformation associated with a maturing manufacturing sector.